The Effect of Attorney Type on Bail Decisions. (February 2017) - Williams, Marian R.
The U.S. Supreme Court has indicated that defendants are entitled to effective assistance of counsel. Despite this, many research studies and anecdotal evidence suggest that defense counsel, particularly appointed counsel, struggles to provide effective assistance, especially with regard to case outcomes. These studies suggest that having appointed counsel negatively affects case outcomes, such as conviction and sentencing, in that those with appointed counsel are more likely to be convicted and/or sentenced to longer incarceration terms. Previous research has largely ignored earlier stages of a case and the effect of type of counsel on these earlier case outcomes. The current study examines the effect of counsel—public defender versus retained—on bail decisions in Florida. Previous research has indicated that bail decisions have an effect on the outcome of a case, so the importance of bail decisions cannot be overlooked.